422. Performance Evaluation of a Rapid and Easy-to-Use COVID-19 Test. (31st December 2020) - Toxopeus, Corike; Jones, Brian; Brown, Jessica; Gurling, Mark; Andjelic, Cynthia; Phillips, Cynthia L
Abstract: Background: The BioFire ® COVID-19 Test is a qualitative test for use on the FilmArray ® 2.0 and Torch systems for the detection of SARS-CoV-2 RNA in nasopharyngeal swabs (NPS) in transport media. This test received Emergency Use Authorization from the FDA. A closed, disposable pouch contains all the necessary reagents for sample preparation, nucleic acid extraction, reverse transcription, polymerase chain reaction (PCR), and amplified nucleic acid detection to identify RNA from SARS-CoV-2 virus in an NPS specimen. Internal controls monitor all stages of the test process. Once an NPS sample (0.3 mL) is loaded into the system disposable pouch (Figure 1), the fully automated test returns results within an hour. As an additional resource, the BioFire ® COVID-19 Test External Control Kit (+) includes positive external control material that may be used for quality control and laboratory verification. Figure 1. BioFire COVID-19 Test Disposable Pouch Methods: The following were evaluated: Limit of Detection (LoD) Positive and Negative Percent Agreement (PPA and NPA, respectively) for clinical contrived samples and a limited number of clinical specimens Exclusivity Results: LoD The LoD was evaluated using live SARS-CoV-2 virus (cultured from the USA_WA1/2020 strain obtained from World Reference Center for Emerging Viruses and Arboviruses (WRCEVA)). The LoD was determined to be 3.3E+02 GC/mL (2.2E-02 TCID50 /mL). Clinical Contrived Accurate detection of virus in clinical matrix was demonstrated at various LoD levels using thirty contrived individual unique clinical samples (PPA), and 66 individual unique negative clinical specimens (NPA). Clinical Samples Positive samples were collected from patients presenting with signs or symptoms of COVID-19, and who were previously identified as positive for SARS-CoV-2 by another EUA test. Negative samples were collected in 2018, and therefore presumed negative for SARS-CoV-2. Exclusivity The potential for cross-reactivity was evaluated for six viruses from the same genetic family as SARS- CoV-2, and for an additional 30 high priority organisms/viruses. No cross-reactivity was observed. Table 1. SARS-CoV-2 Virus Test Results at 1× and 0.1× LoD for the BioFire COVID-19 Test Table 2. Clinical Contrived and Negative Testing with the BioFire COVID-19 Test Table 3. BioFire COVID-19 Test Performance Summary Conclusion: The BioFire COVID-19 Test reliably detects SARS-CoV-2 virus RNA in clinically relevant samples. Disclosures: Corike Toxopeus, PhD, BioFire Defense, LLC. (Employee, stock owner) Brian Jones, PhD., BioFire Defense, LLC (Employee, own stock) Jessica Brown, BS, BioFire Defense (Employee, Stock owner) Mark Gurling, PhD, BioFire Defense, LLC (Employee) Cynthia Andjelic, PhD., BioFire Defense (Employee, Other Financial or Material Support, Own stocks) Cynthia L. Phillips, PhD, BioFire Defense (Employee, Scientific Research Study Investigator, Shareholder)BioFire Defense (Employee, Scientific Research Study Investigator, Shareholder)